Literature Review on the Most Popular of NFTs Types - Oleg Wlasinsky (CV TOPAZART, 2023)
Non-fungible tokens (NFTs) are transferrable rights to digital assets, such as art, in-game items, collectibles, or music. The phenomenon and its markets have grown significantly since early 2021. This study aims to find the most popular NFT type. This study uses a qualitative research method processing data using NVivo with four steps: Gathering information, Coding, running queries and Reporting. We investigate the interrelationships between NFT sales, NFT users (unique active blockchain wallets), and the pricing of Bitcoin and Ethereum. The results reveal that there are 26 published articles in the targeted journals and websites, and they are mainly focused on the popularity area. The research findings show that Collectibles trigger an increase in NFT sales. Also, ether price shocks reduce the number of active NFT wallets. The results show that Collectibles markets affect the growth and development of the NFT marketplace since they are the most popular among NFTs.